Long-term outcomes of pharmacologically treated versus non-treated adults with ADHD and substance use disorder: a naturalistic study - Bihlar Muld, Berit; Bölte, Sven (Journal of substance abuse treatment, 2015)
Background and aims: The pharmacological treatment of individuals with attention deficit hyperactivity disorder (ADHD) and severe substance use disorder (SUD) is controversial, and few studies have examined the long-term psychosocial outcome of these treatments. Our aim was to investigate whether pharmacological treatment was associated with improved long-term psychosocial outcomes. Methods: The present naturalistic study consisted of a long-term follow-up of 60 male patients with ADHD and comorbid severe SUD; all participants had received compulsory inpatient treatment due to severe substance abuse. The average interval between inpatient discharge and follow-up was 18.4months. Thirty patients had received pharmacological treatment for ADHD, and 30 patients were pharmacologically untreated. The groups were compared with respect to mortality and psychosocial outcomes operationalized as substance abuse status, ongoing voluntary rehabilitation, current housing situation and employment status. Results: The groups were comparable with regard to the demographic and background characteristics. Overall, mortality was high; 8.3% of the participants had deceased at follow-up (one in the pharmacologically treated group and four in the untreated group; the between-group difference was not significant). The group that received pharmacological treatment for ADHD exhibited fewer substance abuse relapses, received more frequently voluntary treatments in accordance with a rehabilitation plan, required less frequent compulsory care, were more frequently accommodated in supportive housing or a rehabilitation center, and displayed a higher employment rate than the non-treated group. Conclusions: The recommendations for the close clinical monitoring of high-risk populations and the prevention of misuse and drug diversion were fulfilled in the structured environment of compulsory care for the treated group. Pharmacological treatment of ADHD in individuals with severe SUD may decrease the risk of relapse and increase these patients' ability to follow a non-pharmacological rehabilitation plan, thereby improving their long-term outcomes.